2018
DOI: 10.1038/s41431-018-0211-6
|View full text |Cite
|
Sign up to set email alerts
|

Paternal origin of Paleo-Indians in Siberia: insights from Y-chromosome sequences

Abstract: The expansion of modern humans to the American continent after the Last Glacial Maximum led the way to the present-day distribution of American aborigines. Recent advances in autosomal DNA research and expanded testing of mtDNA lineages has provided a clearer picture of the number and timing of founding lineages. However, both autosomal DNA and mtDNA research have provided unresolved competing theories between the short-term and the long-term models of the Beringian standstill hypothesis. Further, the source o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 65 publications
(185 reference statements)
0
23
0
1
Order By: Relevance
“…As discussed in the section above, most samples of rare C2a‐L1373 sublineages were found in populations from low latitude regions of northern Asia, such as the Amur River region, the Mongolian Plateau, the northern boundary of China, and adjacent areas. Previous studies have also demonstrated that the Amur River region is the urheimat of F1756, M504, and M86, before their expansion in the last several thousand years (Derenko et al, 2006; Duggan et al, 2013; Malyarchuk et al, 2010; Malyarchuk et al, 2013; Wei et al, 2017; Wei, Wang, et al, 2018; Wei, Yan, et al, 2018; Zhang et al, 2018; Zhong et al, 2010). Based on these findings and available ancient DNA (like NEO239 individual of haplogroup C2a2‐MPB373 and the UKY001 individual of C2a1a1a1*‐B473, see Figure 1), we propose that the initial differentiation of C2a‐L1373 began in the low latitude region of northern Asia (likely the Amur River region), and the continuous splitting pattern of C2a‐L1373 between 18 and 14 kya may correspond to the repeopling of northern Asia, from south to north and west, after the LGM.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…As discussed in the section above, most samples of rare C2a‐L1373 sublineages were found in populations from low latitude regions of northern Asia, such as the Amur River region, the Mongolian Plateau, the northern boundary of China, and adjacent areas. Previous studies have also demonstrated that the Amur River region is the urheimat of F1756, M504, and M86, before their expansion in the last several thousand years (Derenko et al, 2006; Duggan et al, 2013; Malyarchuk et al, 2010; Malyarchuk et al, 2013; Wei et al, 2017; Wei, Wang, et al, 2018; Wei, Yan, et al, 2018; Zhang et al, 2018; Zhong et al, 2010). Based on these findings and available ancient DNA (like NEO239 individual of haplogroup C2a2‐MPB373 and the UKY001 individual of C2a1a1a1*‐B473, see Figure 1), we propose that the initial differentiation of C2a‐L1373 began in the low latitude region of northern Asia (likely the Amur River region), and the continuous splitting pattern of C2a‐L1373 between 18 and 14 kya may correspond to the repeopling of northern Asia, from south to north and west, after the LGM.…”
Section: Discussionmentioning
confidence: 94%
“…Due to the high frequencies of F1756, M504, and M86 among modern populations, most previous studies have focused on the expansion process of these three major subbranches of C2a‐L1373 and their role during the formation of proto‐Mongols, modern Mongolic‐speaking populations, and Tungusic‐speaking populations (Derenko et al, 2006; Duggan et al, 2013; Malyarchuk et al, 2010; Malyarchuk et al, 2013; Wei et al, 2017; Wei, Wang, et al, 2018; Wei, Yan, et al, 2018; Zhang et al, 2018; Zhong et al, 2010). In this study, we focused on the early differentiation history of rare subbranches of C2a‐L1373.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations